The Effect of Religiosity Moderation with Loss Aversion on the Investment Decision of Personal Investors Kind of Stock Security in Padang City - Syailendra Eka Saputra; Rizky Natassia; Hayu Yolanda Utami (AMAR (Andalas Management Review), 2020)
This study aims to determine the effect of the value of religiosity that moderates loss aversion on investment decisions taken by individual investors in investing in stock type securities. The study was conducted on 120 individual investors who were chosen at random. The analytical method used is to use moderation analysis which is processed using Smart PLS. The test results found that religiosity does not affect the investment decisions of individual investors on stock type securities, while the loss aversion affects the investment decisions of individual investors on stock type securities. During the hypothesis-testing phase, it was proven that religiosity moderation with loss aversion had a negative and significant influence on the investment decisions of individual investors in the securities of shares in Padang.